POLEMIK LAHIRNYA KONSEP QIRĀ‘AH SAB’AH DALAM DISIPLIN ILMU QIRĀ‘AH - Mustopa, Mustopa (Hunafa: Jurnal Studia Islamika, 2014)
QirÄ'ah is a very important science in the study of the Â UlÅ«m al-Qurâ€˜Än.The importance of this science lies not only onÂ  the mehod of how to recite the Qurâ€™an but also on the method of how to understabd Â the meaning of the Koran. In this regard, understanding the formation of qirÄâ€˜ah Â history in its present formÂ  becomes important, especially Â because Â so rich treasures that the qirÄâ€˜ah possesses that appeared during the codification of official qirÄ'ah. The standardization of this qirÃ¢'ah, on the one hand, gives the muslims a lot ease in reading the Koran; on the other hand, it burries the treasures of the qirÄ'ah science very dynamic during qirÄ'ah sab'ah codification. This paper discusses the crucial issues related to qirÄâ€˜ah, including the dark side of its birth to the critical and the objective reading towards the science.Kata Kunci: Aá¸¥ruf, QirÄâ€˜ah Sabâ€™ah, QirÄâ€˜ah â€˜Asyrah, riwayat, kodifikasi (tadwÄ«n)